Cross sectional study to evaluate modified Alvardo score in the diagnosis of acute appendicitis - Dutta, Pramatha Nath; Chatterjee, Ranadip; Das, Tamoghna; Bag, Lita; Bhaumik, Purba (International Journal of Clinical Trials, 2023)
Background: Appendectomy is one of the most commonly performed emergency operation. The diagnosis requires distinguishing from other causes of pain in that region of the abdomen like acute ureteric colic, right sided salphingoophoritis. Presently ultrasonogram and contrast enhanced CT scan are the diagnostic modalities of choice. Although these facilities are readily available in urban areas but rural areas still suffer from lack of timely diagnosis and negative appendectomy, enhancing the need for a reliable scoring system for diagnosis of acute appendicitis. Here we will evaluate modified Alvardo scoring system in diagnosis of acute appendicitis. Methods: This is an observational cross-sectional hospital-based study at KPC medical college, Kolkata with 92 consecutive cases of suspected acute appendicitis, who were admitted, investigated and treated during 1st February 2022 to 31st January, 2023. Modified Alvardo score is calculated of each patient and compared with the histopathological findings of operated appendix. Results: The above study shows that modified Alvardo score 7-9 has high sensitivity of 93.10% in men and in female sensitivity is 77.78%. Overall sensitivity of modified Alvardo score of 7-9 came out to be 83.63%. Conclusions: It can be concluded that modified Alvardo score of 7-9 can be used as a potent diagnostic tool in male. But in females due to lower sensitivity and significant number of negative appendectomy, it can be used an diagnostic aid in addition to imaging studies for diagnosis.